COMPETITIVENESS-MAPPING OF RESTAURANTS BASED ON ITS PRODUCT AS A REFERENCE OF CULINARY TOURISM OBJECTS - Kristian Suhartadi Widi Nugraha; Ika Barokah Suryaningsih (Manajemen dan Bisnis, 2017)
This research is conducted to analyze the map positioning product attributes of Lestari restaurant and the competitors in Jember Regency. The basis used to determine the position of the restaurants is consumers’ perceptions regarding to the similarity of determinant attributes consisting of price, convenience, human resources services, taste quality, menu variants, location of each restaurant. The analysis technique is Multidimensional Scaling (MDS). This research was conducted by taking respondents as many as 60 respondents with purposive sampling method. The results of the restaurant positioning map (Lestari, Terapung, Legian, Wong Solo, Bu Lanny) are based on consumer perceptions and the similarity of respondents' attitudes in giving the assessment. Based on the analysis, there are differences in the position of each restaurant based on consumer perceptions and it shows that Lestari restaurant is direct competitor from Terapung restaurants, Wong Solo and Bu Lanny which do not have a strong or clear positioning, because they do not have many similarities and differences with other restaurants in the minds of consumers. Lestari and Legian restaurants are direct competitors because they have clear and unique differentiation. Therefore, Lestari restaurant in Jember Regency has a strong competitiveness in the market that comes from product attributes, namely the quality of taste and menu variants. The results of the consistency and similarity tests of respondents' attitudes also showed that the respondents did not have the same attitude in assessing the similarity of restaurants in Jember Regency.